Tense and Text in Classical Arabic - Marmorstein, Michal (Brill, 2018)
This study undertakes to examine the problem of the tenses in Classical Arabic. While aware of the long tradition which shaped the discussion of this subject, and building, in fact, on some important insights offered by medieval and modern grammarians, this study attempts to redefine the discussion and propose a new analysis of the tenses, based on a functional text-oriented investigation of a large corpus of Classical Arabic prose.